2021
DOI: 10.1007/s00425-021-03749-3
|View full text |Cite
|
Sign up to set email alerts
|

Late-maturity α-amylase (LMA): exploring the underlying mechanisms and end-use quality effects in wheat

Abstract: Main conclusion A comprehensive understanding of LMA from the underlying molecular aspects to the end-use quality effects will greatly benefit the global wheat industry and those whose livelihoods depend upon it. Abstract Late-maturity α-amylase (LMA) leads to the expression and protein accumulation of high pI α-amylases during late grain development. This α-amylase is maintained through harvest and leads to an unacceptable low falling number (FN),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 141 publications
(285 reference statements)
0
17
0
Order By: Relevance
“…Even though LMA trait is a genetic defect, it persists in wheat germplasm implying that it is either not selected against or alternatively imparts unbeknown beneficial attributes to LMA-prone varieties (24). By unravelling the genetic, biochemical, and physiological mechanisms that lead to LMA expression, scientists strive to understand and eliminate LMA from wheat breeding programs (39). Surprisingly, post-genomics is not one of the strategies adopted by researchers to close the biological knowledge gap, with only one transcriptomics study registered so far (22).…”
Section: Application To a Wheat Industry Problem: Late Maturity Alpha...mentioning
confidence: 99%
See 1 more Smart Citation
“…Even though LMA trait is a genetic defect, it persists in wheat germplasm implying that it is either not selected against or alternatively imparts unbeknown beneficial attributes to LMA-prone varieties (24). By unravelling the genetic, biochemical, and physiological mechanisms that lead to LMA expression, scientists strive to understand and eliminate LMA from wheat breeding programs (39). Surprisingly, post-genomics is not one of the strategies adopted by researchers to close the biological knowledge gap, with only one transcriptomics study registered so far (22).…”
Section: Application To a Wheat Industry Problem: Late Maturity Alpha...mentioning
confidence: 99%
“…A single unit corresponds to the amount of enzyme required to release 1 µM p-nitrophenyl in the presence of excess quantities of alpha-glucosidase in 1 min at 40°C (38). Such measurements have revealed that LMA is more prevalent than originally thought, with reports arising from North America, Australia, Japan, Canada, South Africa, China, Mexico, Germany, and the United Kingdom (39). The presence of LMA in breeding populations could be attributed to unexplained positive effects on grain production/quality or alternately simply manifest the lack of significant selection pressure against this trait (24).…”
Section: Introductionmentioning
confidence: 99%
“…There is lack of correlation between LMA FN and end‐product quality (Neoh et al., 2020). It is questionable if there is a correlation, especially when α‐amylase level is not very high (Cannon et al., 2021). Although both PHS and LMA result in elevated high pI α‐amylase levels, LMA results in TaAmy1 mRNA induction, whereas PHS results in the induction of TaAmy1 , TaAmy2 , and TaAmy4 transcripts (Barrero et al., 2013; Mieog et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…If the α‐amylase levels are significantly higher in the embryo proximal half than in the distal half, the cause is PHS. Less is known about the biochemical mechanisms controlling cell death during LMA and whether they are exactly the same as those observed during germination (Cannon et al., 2021). Studies of LMA‐susceptible wheat lines suggested that LMA induction was associated with randomly spaced patches of cell death throughout the distal‐to‐proximal length of the aleurone layer, suggesting that α‐amylase induction during LMA is associated with programmed cell death just as it is during germination (Mrva et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…LMA has recently received much attention and been differentiated from PHSing by the location of α‐amylase activity in the grain. The impact of LMA on wheat and baking quality is fairly limited and inconsistent (Cannon et al, 2022; Newberry et al, 2018), and thus in need of further study.…”
Section: Introductionmentioning
confidence: 99%